Factors associated with the contraindicated use of oral contraceptives in Brazil - Daniele Aparecida Silva Corrêa; Mariana Santos Felisbino-Mendes; Mayara Santos Mendes; Deborah Carvalho Malta; Gustavo Velasquez-Melendez
ABSTRACT OBJECTIVE To estimate the prevalence of the contraindicated use of oral contraceptives and the associated factors in Brazilian women. METHODS 20,454 women who answered the VIGITEL survey in 2008 also participated in this study, of which 3,985 reported using oral contraceptives. We defined the following conditions for the contraindicated use of contraceptives: hypertension; cardiovascular diseases such as heart attack, stroke/cerebrovascular accident; diabetes mellitus; being smoker and 35 years old or older. We estimated the prevalence and 95% confidence intervals of contraindicated use in users of oral contraceptives and the factors associated with contraindication by prevalence ratio and 95% confidence intervals. RESULTS In the total population, 21% (95%CI 19.7-21.9) of women showed some contraindication to the use of oral contraceptives, of which 11.7% (95%CI 10.6-13.7) belonged to the group of users of oral contraceptives. The most frequent contraindication in users of oral contraceptives was hypertension (9.1%). The largest proportion of women with at least one contraindication was aged between 45 and 49 years (45.8%) and with education level between zero and eight years (23.8%). The prevalence of contraindication to oral contraceptives was higher in women less educated (zero to eight years of study) (PR = 2.46; 95%CI 1.57-3.86; p < 0.05) and with age between 35-44 years (PR = 4.00; 95%CI 2.34-6.83) and 45-49 years (PR = 5.59; 95%CI 2.90-10.75). CONCLUSIONS Age greater than or equal to 35 and low education level were demographic and iniquity factors, respectively, in the contraindicated use of oral contraceptives.